Briquettes Made from Wood Residues - Brožek, Milan (Manufacturing Technology Journal, 2015)
At logging and at the subsequent wood and wood semi-products treatment and also at fruit trees treatment the fine grained loose waste is arising, e.g. wood dust, saw dust, shavings, chips, bark etc. One of possibilities of its meaningful utilization is the briquetting technology, which product are briquettes determined for energetic utilization (combustion). In the paper the experimental results are published. The briquettes quality evaluation was their aim. For the tests pine bark chips, fir chips, spruce shavings, spruce sawdust, apple chips and cherry chips were used The basic physical-mechanical properties were the evaluation criteria. Following properties were determined: ash amount, gross calorific value, total moisture content, density, rupture force, length, diameter, weight and mechanical durability.
Keywords: wood; briquetting; wood briquettes; density; rupture force